White matter connectivity in neonates at risk of stuttering: Preliminary data. (11th June 2022) - Packman, Ann; Onslow, Mark; Lagopoulos, Jim; Shan, Zack Y.; Lowe, Robyn; Jones, Monique; O'Brian, Sue; Sommer, Martin
Highlights: The cause of developmental stuttering is not fully understood. Impaired white matter fibre myelination has been detected. It has not been established whether this is causal and not a result of stuttering. Hence, we scanned the brains of neonates genetically at risk of stuttering. Findings suggest a causal factor in developmental stuttering. Abstract: Background: Developmental stuttering is thought to be underpinned by structural impairments in the brain. The only way to support the claim that these are causal is to determine if they are present before onset. Materials and methods: Magnetic resonance imaging (MRI) was conducted on 18 neonates, aged 8–18 weeks, 6 of whom were determined to be genetically at risk of stuttering. Results: With tract-based spatial statistics (TBSS) analysis, no statistically significant differences were found between the at-risk group and the control group. However, fractional anisotropy (FA), mean diffusivity (MD), and radial diffusivity (RD) in the corpus callosum of the at-risk group were lower (uncorrected) than in the control group. Automated Fiber Quantification (AFQ) yielded lower FA in the at-risk group than in the control group in the medial section of the callosum forceps minor. Discussion: The findings, albeit with a small number of participants, support the proposition that reduced integrity of white matter in the corpus callosum has a causal role in developmental stuttering. Longitudinal research to determine if children with this impairment at birth later start to stutter is needed to confirm this. The left arcuate fasciculus is thought to develop as speech develops, which likely explains why there were no abnormal findings in this area in our at-risk neonates so soon after birth. This is the first study to investigate the brains of children before the onset of stuttering, and the findings warrant further research.